The level of knowledge, attitude and practice on complementary feeding among caregivers in Kampung Jeriah, Sibu, Sarawak from 23rd September 2013 to 8th December 2013 - Athira, binti Abu Bakar; Bellarmine, anak Intai; Felicity, anak Lawrence Ghundy; Kean, Lim Fong; Mohamad Fayyadh, b Mohd Mokhtar; Nur Azzah Azyyaty, binti Mazlan; Shirley Diane, anak Belor; Aida Fadzlyna, binti Jamaludin @ Ali; Chuan, Albert Moh Shan; Amutha Malar, a/p Sanmugam; Anwar Hasif, bin Abdul Ramit; Ken, Chan Kok; et al. (Universiti Malaysia Sarawak (UNIMAS), 2013)
Background: The period for complementary feeding is crucial for young infants. Lack of awareness in knowledge, attitude and practice towards complementary feeding among caregivers will lead to improper practice of complementary feeding which may affect the health of children under their care. Objective: The purpose of this study is to determine the level of knowledge, attitude, and practice (KAP) on complementary feeding among caregivers in Kampung Jeriah, Sibu, Sarawak. Methods: This is a cross-sectional study done among 60 caregivers in Kampung Jeriah, Sibu, Sarawak. Non-probability sampling method was adopted to select at least one caregiver from each household in the village. A self-administered style of data collection was used. The data was analysed for descriptive data of mean, median, frequencies and standard deviation using SPSS version 20.0. Results: Among the respondents, the levels of KAP are 61.7%, 50% and 60% respectively. In this study, the respondents with lower income have significantly better knowledge regarding complementary feeding (p=0.01). The results also showed that respondents aged 25-44 years old had good practice towards complementary feeding as compared to younger or older group, which is reflected in the p value 0.032. Almost half of the respondents with good level of knowledge (48.6%) started to give complementary food to their child at age 6 months old. Conclusion: Generally, the respondents had a satisfactory level of knowledge and practices towards complementary feeding. However. the level of attitude on complementary feeding was relatively low compared to the level of knowledge and practice. Statistically, there was no significant correlation between the three components (knowledge, attitude and practice on complementary feeding). It was recommended that more health education should be held by the health authority on complementary feeding so that the knowledge, attitude and practice of caregivers on the topic could be improved. III